Memeta Tipe Sekulerisme Islam di Indonesia 1920-1945 Sebagai Landasan Dakwah - Indrawati, Indrawati (INTELEKSIA: Jurnal Pengembangan Ilmu Dakwah, 2023)
MAPPING THE TYPES OF ISLAMIC SECULERACY IN INDONESIA 1920-1945 AS A BASIS OF DAKWAH. The discourse on Islamic secularism in Indonesia is interesting to study from various points of view/approaches because of its debatable characteristics, including from a historical approach over a fairly long period of time. The focus of this study is to identify the type of Islamic secularism in Indonesia between 1920-1945, is it hard secularism or soft secularism? The study approach used is library research, while the theory uses Alfred Stepan's Twin Tolerance theory. This theory has the principle that there is never a clear separation of politics and religion, but rather the provision of space between the two sides of religion and politics in managing each other's affairs within certain limits, which has become known as twin tolerance. However, the priority of this study is to look at Islamic secularism from the political field only, but not religion because it requires its own focus. The results of the study show that from 1920-1945, the type of Islamic secularism found in Indonesia was hard secularism because the space for religious tolerance in regulating political affairs was quite limited.